A Comprehensive Physical, Chemical and Morphological Characterization of Novel Cellulosic Fiber Extracted from the Stem of Elettaria Cardamomum Plant. Issue 10 (3rd October 2021) - Ahmed, Javeed; Balaji, M.A.; Saravanakumar, S.S.; Senthamaraikannan, P.
ABSTRACT: To overcome the environmental regulations adopted across the globe in polymer composites, a natural fiber extracted from the waste stem of Elettaria cardamomum plant (ECF) was investigated for its suitability in polymer composites. Fundamental properties such as chemical, physical, thermal and surface morphology of ECF were evaluated using chemical composition analysis, optical microscope test, X-ray diffraction, Thermo-gravimetric and scanning electron microscope analysis. The chemical analysis outcomes revealed that ECF has a comparatively higher amount of cellulose (63.12 wt. %), lignin (16.5 wt. %) and lower hemicelluloses (13.7 wt. %), wax (1.5 wt. %) which is expected property of a reinforcement. Thermal analysis results demonstrated that ECF has thermal stability (up to 230°C). Surface morphological analysis showed that non-cellulosic materials and impurities existed on the surface of the ECF. So, mild surface treatment was recommended. Higher tensile strength (294 ± 1.62 MPa) and lower density (1470 Kg/m 3 ) of ECF defined this as an appropriate fiber for reinforced composites.